How to Plan Advertising / Second Edtion - Cooper Alan (Cassell, 1997)
A clear, informative and entertaining book, written for anyone who is interested in the way in which advertising is developed in agencies. Acknowledgements, Introduction, The Planning Context, The Role for Advertising, Developing Advertising Strategy, Creative Briefs and Briefings, The Requirements for Creativity: A Creative Director's Perspective, Creative Development Research, Campaign Evaluation, Account Planning and Media Planning, International Account Planning, Planning Inputs Into the Client's Business, Planning in Other Communications Industries, Notes and References, Index.